2006
DOI: 10.1091/mbc.e06-06-0516
|View full text |Cite
|
Sign up to set email alerts
|

Top3 Processes Recombination Intermediates and Modulates Checkpoint Activity after DNA Damage

Abstract: Mutation of TOP3 in Saccharomyces cerevisiae causes poor growth, hyperrecombination, and a failure to fully activate DNA damage checkpoints in S phase. Here, we report that overexpression of a dominant-negative allele of TOP3, TOP3 Y356F , which lacks the catalytic (decatenation) activity of Top3, causes impaired S-phase progression and the persistence of abnormal DNA structures (X-shaped DNA molecules) after exposure to methylmethanesulfonate. The impaired S-phase progression is due to a persistent checkpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
59
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 56 publications
13
59
0
Order By: Relevance
“…This prolongation of S-phase by MMS (relative to unperturbed cells) is a consequence of MMS-induced replication fork stalling and subsequent checkpoint activation (Paulovich and Hartwell, 1995;Santocanale and Diffley, 1998;Shirahige et al, 1998;Tercero and Diffley, 2001). In agreement with our previous data (Mankouri and Hickson, 2006), rad51 cells failed to completely traverse S-phase by 4 h in the presence of 0.0167% MMS, demonstrating a mid-Sphase DNA content at 4 h ( Figure 2B). Interestingly, we observed that rad54 and shu1 mutants resembled rad51 mutants and also failed to traverse S-phase by 4 h in 0.0167% MMS ( Figure 2B).…”
supporting
confidence: 93%
See 3 more Smart Citations
“…This prolongation of S-phase by MMS (relative to unperturbed cells) is a consequence of MMS-induced replication fork stalling and subsequent checkpoint activation (Paulovich and Hartwell, 1995;Santocanale and Diffley, 1998;Shirahige et al, 1998;Tercero and Diffley, 2001). In agreement with our previous data (Mankouri and Hickson, 2006), rad51 cells failed to completely traverse S-phase by 4 h in the presence of 0.0167% MMS, demonstrating a mid-Sphase DNA content at 4 h ( Figure 2B). Interestingly, we observed that rad54 and shu1 mutants resembled rad51 mutants and also failed to traverse S-phase by 4 h in 0.0167% MMS ( Figure 2B).…”
supporting
confidence: 93%
“…Plates were grown at 30°C. The large single colonies that arise in strains overexpressing TOP3 Y356F represent suppressors (probably SGS1-linked) as seen previously (Oakley et al, 2002;Mankouri and Hickson, 2006). (B) Wild-type, shu1, rad51, rad51shu1, rad54, and rad54shu1 strains were diluted to equivalent densities and spotted onto control plates (no drug) or plates containing MMS.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…In particular, Sgs1 and Top3 are suggested to resolve recombination structures originating from sister chromatid junctions at damaged replication forks, while Srs2 prevents their formation (Liberi et al, 2005;Mankouri and Hickson, 2006;Mankouri et al, 2007). mph1 mutants are not deficient in HR, as determination of spontaneous mitotic recombination rates demonstrated.…”
Section: Mph1 Probably Acts At a Stage After Initiation Of Recombinationmentioning
confidence: 99%